A PERMA-Based Measure of Student Well-Being in Science Learning: Development and CFA Validation - Utami, Asih; Ghufroni Farid, Mohammad; Natalina, Kristiani; Trisnani, Novy; Yunaini, Norma; Adelia, Siska; Nur Ilham, Zain (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2026)
Student well-being is essential for effective and sustainable science learning. However, no instrument has specifically assessed it based on this context’s PERMA (Positive Emotion, Engagement, Relationships, Meaning, and Accomplishment) model. This study aims to develop and validate a PERMA-based well-being instrument for secondary school students. The instrument was developed through three phases: item generation and expert validation, pilot testing, and scale evaluation using Confirmatory Factor Analysis (CFA). Data were collected from secondary school students and analysed using the Maximum Likelihood Robust (MLR) estimator. The five-factor model demonstrated good fit (χ²/df = 2.01; RMSEA = 0.055; CFI = 0.964; TLI = 0.957) and met convergent validity, discriminant validity, and construct reliability criteria. The instrument is valid, reliable, and sensitive to the science learning context, supporting and integrating social-emotional learning in STEM education to enhance student well-being.